Vittorio Guidano’s trips to Argentina (1989-1999) - Barahona-Moore, Jorge Sebastián; Klappenbach, Hugo; Scholten, Hernán; Salas, Gonzalo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
The present article aims to narrate the trips of the Italian psychiatrist Vittorio Guidano (1944-1999) to Argentina during the 1990s. In order to highlight the impact of the activities he carried out within the framework of his visits, mainly conferences and seminars, a brief presentation of the evolution of Guidano's thought, which led him to elaborate a post-rationalist psychotherapy, is outlined. His interest in spreading his proposal, joined with a group of Argentine psychotherapists, who were already interested in the ideas of Hans Eysenck and Aaron Beck, led to a special episode in the history of modern psychology. Indeed, the impact of the Italian psychiatrist's approach among these young professionals, who were looking for new perspectives for their clinical practice, had consequences that can be traced in Argentine therapeutic circles up to the present day.